INDIVIDUAL DIFFERENCES IN REASONING AND PROBLEM SOLVING BY SELF-GENERATION OF EXTERNAL REPRESENTATIONS - Nguyen, Trang (My University, 2020)
This study aimed at exploring the variation in representational preferences in reasoning and solving textual problems under the influence of individual differences. For that purpose, survey, interview and observation were employed to explore how problem solvers solved problems differently in terms of the self-generation of different representations and whether their life-time activities related to the problem solving behaviors and outcomes. Ten different specific representational styles were identified from subjects’ written performances corresponding to two main tendencies, namely, solving problems with selfconstruction of external representations (57%) and solving problems internally (43%). There were three sub-categories for external representations, namely, verbal, diagrammatic-graphical and mixed external representations. The self-construction of external representations found justified by memory factor, the need of visualization, the need of making sense and simplifying information and information-based factor. The use of an external representation related strongly with successful outcomes from the problem perspective but not from the subjectcentered analysis. This indicates that the relationship between the use of external representations and problems’ performance is complicated. Finally, there was no clear evidence for the association between the frequent participation in real-life activities and problem solving behaviors and outcomes in respect of self-construction of external representations. Important conclusions drawn from this study is the tendencies towards constructing and effective external representations involved several dimensions, namely, a problem’s nature and demand triggering the constructing, a subject’s characteristics affecting their preferences and capabilities of a certain representations.
Keywords: Reasoning and problem solving, external representations, individual differences